The Effect of the Combination of Herbal Concoction and Seaweed Flour (Gracilaria sp) on Carcass Percentage, Carcass Components, and Abdominal Fatness of Broiler Chickens - Salido, Wa Laili; Tatra, Afsitin Joan; Safaat, La Ode Muh (DEPARTMENT OF ANIMAL HUSBANDRY, FACULTY OF AGRICULTURE, UNIVERSITY OF LAMPUNG, 2025)
The research aims to examine the effect of giving a combination herbal concoctions and seaweed flour (Gracilaria sp) on carcass percentage, carcass parts and abdominal fat in broiler chickens. The material used was 100 broiler chickens kept from one day of age (DOC) to 35 days of age. Each chicken is placed in a single cage, each cage has a place for drinking water and food. The treatments in this study consisted of: P0: Commercial feed + 0% herbal ingredients + 0% seaweed flour, P1: Commercial feed + 1% herbal ingredients + 1% seaweed flour, P2: Commercial feed + 2% herbal ingredients + 2 % seaweed flour, P3: Commercial feed + 3% herbal ingredients + 3% seaweed flour. All data were analyzed using analysis of variance and different between treatments were proved using Duncan multiple range test. combination of herbal concoctions and seaweed flour (Gracilaria sp) to the feed had a significant effect (P<0.05) on the percentage of carcass parts (thighs) and abdominal fat in broilers, but had no significant effect (P>0.05) on the percentage carcass, carcass parts (breast, back and wings) for all treatments. The conclusion of the research is that combination of herbal ingredients and seaweed flour can reduce abdominal fatness levels and improve the percentage of broiler carcass components.